Convenient one-step Synthesis of Substituted Pyrano[2,3-c]isoquinoline (2-amino-4H-chromenes) via three Component Reaction between Alkyl isocyanides and Dialkyl Acetylenedicarboxylate in the presence of 3-Hydroxyisoquinoline (JOURNAL OF ADVANCES IN CHEMISTRY, 2010)
The reactive intermediate generated by the addition of alkyl isocyanides to dialkyl acetylenedicarboxylate are trapped by 3-hydroxyisoquinoline to produce highly functionalized 4H-chromenes in 83-92% yields.